Unshrinking the baby lung to calm the VILI vortex - Gary Nieman; Michaela Kollisch-Singule; Harry Ramcharran; Joshua Satalin; Sarah Blair; Louis A. Gatto; Penny Andrews; Auyon Ghosh; David W. Kaczka; Donald Gaver; Jason Bates; Nader M. Habashi (Critical Care, 2022)
Abstract A hallmark of ARDS is progressive shrinking of the ‘baby lung,’ now referred to as the ventilator-induced lung injury (VILI) ‘vortex.’ Reducing the risk of the VILI vortex is the goal of current ventilation strategies; unfortunately, this goal has not been achieved nor has mortality been reduced. However, the temporal aspects of a mechanical breath have not been considered. A brief expiration prevents alveolar collapse, and an extended inspiration can recruit the atelectatic lung over hours. Time-controlled adaptive ventilation (TCAV) is a novel ventilator approach to achieve these goals, since it considers many of the temporal aspects of dynamic lung mechanics.